Risk factors of acute malnutrition among children aged 6-59 months enrolled in a community-based programme in Kurigram, Bangladesh: a mixed-method matched case-control study - Monsurul Hoq; Masum Ali; Ashraful Islam; Charulatha Banerjee (BMC, 2019)
Abstract Background Risk factors of acute malnutrition in Bangladesh are well documented. However, due to regional variations in prevalence of acute malnutrition, it is important to explore the risk factors specific to the region, for designing and implementing public health interventions. Methods A mixed-method matched case-control study was conducted in the Kurigram district of Bangladesh. Community perspectives on causes of acute malnutrition were collected from 75 purposively selected caregivers through interviews, focus group discussions and informal group discussions. The data was analysed manually by coding and sub-coding according to different themes. Caregivers of 52 malnourished and 95 well-nourished children matched in age group and sex with the malnourished children, were interviewed using a structured questionnaire. The conditional logistic regression analysis was performed to identify the risk factors of acute malnutrition. Results Caregivers perceived inappropriate feeding practice as a major cause of acute malnutrition whereas birth order (first child OR 0.3, 95% CI 0.09, 0.96), number of family members (OR 1.30, 95% CI 1.02, 1.65), illness in the last 2 weeks (OR 3.08, 95% CI 1.13, 8.42) and access to hygienic latrine (OR 0.25, 95% CI 0.07, 0.82) were also associated with acute malnutrition among children under five in Kurigram. Conclusions Community awareness on infant feeding practices and family planning, management of childhood illness and access to hygienic latrine facilities should be prioritised to prevent acute malnutrition in the northern districts.